Horizon obstruction computed from a digital elevation model - Weber, Eliseu José; Fontana, Denise Cybis (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the accuracy of the horizon obstruction calculation, from a digital elevation model (DEM), at different topographic situations. The material used included an available DEM for the Serra Gaúcha region, RS, Brazil, GPS receivers, a digital camera, wide angle lens, and Idrisi, Arcview/ArcGIS and Solar Analyst softwares. For 16 locations in the study area, hemispherical photographs were acquired and coordinates were collected. Coordinates and DEM were used to calculate the horizon obstruction using the Solar Analyst algorithm. The open sky fraction computed from the DEM and obtained by hemispherical photograph were compared. Determination coefficient was 0.8428, and an average overestimation of 5.53% of the open sky fraction was observed. Errors are mainly attributed to obstruction caused by vegetation, which cannot be identified by the DEM. The horizon obstruction caused by relief in Serra Gaúcha can be computed satisfactorily by the Solar Analyst, from a DEM interpolated from topographical charts at 1:50,000 scale.